Is one nerve transfer enough? A systematic review and pooled analysis comparing ulnar fascicular nerve transfer and double ulnar and median fascicular nerve transfer for restoration of elbow flexion after traumatic brachial plexus injury. Issue 3 (22nd November 2019) - Donnelly, Megan R.; Rezzadeh, Kevin T.; Vieira, Dorice; Daar, David; Hacquebord, Jacques
Abstract: Objectives: Double fascicular transfer is argued to result in improved elbow flexion compared to the traditional ulnar fascicular transfer because it reinnervates both the biceps and the brachialis. This study seeks to determine if double fascicular transfer should be preferred over ulnar fascicular transfer to restore elbow flexion in patients with upper trunk brachial plexus injuries (BPI) by analyzing the current database of literature on the topic. Methods: A systematic review was conducted according to PRISMA guidelines. Inclusion criteria were studies reporting Medical Research Council (MRC) scores on individual patients undergoing ulnar fascicular transfer and double fascicular transfer (ulnar and median nerve fascicle donors). Patients were excluded if: age < 18 years old and follow‐up <12 months. Demographics obtained include age, sex, extent of injury (C5‐C6/C5‐C7), preoperative interval, procedure type, and follow‐up time. Outcomes included absolute MRC score and ability to achieve MRC score ≥3 and ≥4. Univariate and multivariate regression analyses were completed to evaluate predictors of postoperative outcomes. Results: Eighteen studies (176 patients) were included for pooled analysis. Patients that underwent double fascicular transfer had a higher percentage of patients attain a MRC score ≥ 4 compared to ulnar fascicular transfer subjects (83.0% vs. 63.3%, p = .013). Double fascicular transfer was a predictor of achieving high MRC scores (OR = 2.829, p = .015). Multivariate analysis showed that procedure type was the only near significant predictor of ability to obtain MRC ≥4 (OR: 2.338, p = .054). Conclusions: This analysis demonstrates that double fascicular transfer is associated with superior postoperative outcomes and should be performed for restoring elbow flexion.